A (in)efetividade do controle democrático da administração pública: uma abordagem a partir do caso do Conselho Estadual de Saúde do Rio Grande do Sul - Santos, Graciele Mafalda dos (Universidade do Vale do Rio dos Sinos, 2010)
In the face of a situation in which the classic control of Public Administration shows itself inefficient when coping with the daily episodes of mismanagement and corruption involving the State machine and, together with the crisis of the representative democracy, greater management capacity, control and political decision become urgent on the basis of society. In this sense, this study unveils the understanding that the consolidation of the democratic project in Brazil might be attained through the acceptance of the Participatory Democracy in its supplementary relationship with the instruments of representation. This work analyzes the importance of popular participation in the management and in the control of public resources, emphasizing its virtues as well as its existing limits. This paper researches on historical aspects arising from the Iberian culture, whose main political consequences derive from the assimilation of the patrimonial, clientele and authoritarian vices into the Brazilian scenery. It also analyses the current anachronism of the instruments used by the representative democracy, which is permeated by the interference of economic power, the power of the media on the voters, the weakness of political parties, and the lack of synchrony between the expectations of those represented and the performance of their representatives. For that reason, it is proven that social control is still fragile. Seeking a link between theory and practice, this dissertation pondered the (in) effectiveness of democratic control in the contemporary experience of the participatory democracy. This analysis departs from an approach to the health theme on the limits and potentialities of the work carried out by the Conselho Estadual de Saúde do Rio Grande do Sul. A practical study about social control is conducted through a critical analysis of the specific factors that may contribute to the qualification of the Brazilian democratic project, hoping to lead our country to another level of political and social development and to build a more just and egalitarian society.
Keywords: Controle social; Conselho Estadual de Saúde; Democracia participativa; Democracia representativa; Participação popular; Social control; State Board of Health; Participatory democracy; Representative democracy; Popular participation; ACCNPQ::Ciências Sociais Aplicadas::Direito